Fostering Competition in China's Power Markets - Berrah, Noureddine; Lamech, Ranjit; Zhao, Zhao (Washington, DC: World Bank, 2013)
This report proposes a strategy for developing competitive pool markets in China's power sector and for increasing energy trade between competitive pool markets areas. A three-stage approach is offered for developing the competitive pool markets. During stage 1, a mandatory competitive pool will be created with a single buyer. During stage 2, wholesale competition will be permitted. During stage 3, retail competition will be allowed, making the market fully competitive. The staged approach allows competitive market principles to be introduced immediately within existing institutions. This will allow needed skills and parallel economic reforms to be developed gradually and so facilitate increased competition in the later stages. The report also discusses key elemetns of competitive market development, including the organization of transmission services and transition issues such as dealing with stranded costs and mitigating market power among generators.